Fecal Occult Blood Test Results of the National Colorectal Cancer Screening Program in South Korea (2006–2013) - Rim, John Hoon (Sci Rep, 2017)
There has been controversy regarding the clinical utility of fecal occult blood test (FOBT) as a screening tool for colorectal cancer (CRC) in the general population. The purpose of this study was to examine the results of Korea national CRC screening using FOBT from 2006 to 2013 and to evaluate the implementation of the program. We analyzed the results of FOBT, colonoscopy, and the side effects during colonoscopy for the subjects (n = 20,609,909) from the Korea National Health Insurance Cancer Screening database. For evaluation of Korea national CRC screening program implementation over the 8-year period, we calculated uptake rate, FOBT positivity rate, and subsequent test compliance rate. The overall uptake rate was 30.1%, with an increasing pattern from 2006 to 2011. A relatively higher FOBT positivity rate (6.4%) and lower subsequent test compliance rate (46.6%) were observed in comparison to the results previously reported in Western countries. Side effects reported within 3 months period after colonoscopy accounted for 0.17% of all procedures, with bleeding being the most prevalent type. Although the implementation of CRC screening program using FOBT in Korea seems successful, trends in key indicators for Korea national CRC screening program should be monitored continuously.